Effect of conjoint bio-organic and inorganic nutrient sources on plant growth, leaf nutrient content and soil properties of peach (Prunus persica) - SOLANKI, S P S; SHARMA, NAVEEN C; CHANDEL, J S; KUMAR, PRAMOD (The Indian Journal of Agricultural Sciences, 2019)
The present investigation was carried out to find out the effect of conjoint organic and inorganic nutrient source on plant growth, leaf nutrient content and soil fertility status of peach (Prunus persica L. Batsch). The 9-years old trees of uniform size and vigour, planted at 4 × 2 m spacing were selected for the studies. The experiment was laid out in a randomized block design with 11 different conjoint treatment combinations. Maximum increase in plant height (26.69%), canopy diameter (18.01%), tree spread (15.46%), tree canopy volume (52.72%), annual shoot growth (52.32 cm) and leaf area (32.17 cm2) were recorded in trees supplemented with 75% recommended dose of fertilizers (RDF) + vermicompost at 15 kg/tree treatment combination. Leaf N (2.46%), K (1.35%), Mg (0.57%), Cu (11.54 ppm), Fe (224.20 ppm) and Zn (26.14 ppm) were significantly increased in 75% RDF + vermicompost 15 kg/tree treatment application, whereas leaf Ca (1.67%) was higher in trees supplied with 50% recommended dose of fertilizers + vermicompost 30 kg/tree. Maximum available N (279.96 kg/ha) was recorded in treatment combination of 75% RDF + vermicompost 15 kg/tree, however, the conjoint application of nutrient supplemented with 50% RDF + vermicompost 30 kg /tree exhibited significantly higher organic carbon (1.96%), available P (73.39 kg/ha), bacterialcount (43.99 × 10-7 cfu/g) and fungi (7.96 × 10-4 cfu/g) compared to control.